2020
DOI: 10.1007/s00330-020-07480-7
|View full text |Cite
|
Sign up to set email alerts
|

Smart chest X-ray worklist prioritization using artificial intelligence: a clinical workflow simulation

Abstract: Objective The aim is to evaluate whether smart worklist prioritization by artificial intelligence (AI) can optimize the radiology workflow and reduce report turnaround times (RTATs) for critical findings in chest radiographs (CXRs). Furthermore, we investigate a method to counteract the effect of false negative predictions by AI—resulting in an extremely and dangerously long RTAT, as CXRs are sorted to the end of the worklist. Methods We developed a simula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 13 publications
1
22
0
Order By: Relevance
“…This can be partly explained by the fact that it is a "high-level" term, often not mentioning concrete ML algorithms or models in a clear context. Examples of AI in medicine are AI applications to support diagnostic procedures, predict the course of the disease [13][14][15][16][17], enhance the potential of clinical decision support [18], and support the management of hospital workflows [19,20]. Thereby, AI offers the possibility to support physicians in delivering high-quality medicine and increasing medical care efficiency.…”
Section: Big Data and Ai In Medicine: Definition And Application Areasmentioning
confidence: 99%
“…This can be partly explained by the fact that it is a "high-level" term, often not mentioning concrete ML algorithms or models in a clear context. Examples of AI in medicine are AI applications to support diagnostic procedures, predict the course of the disease [13][14][15][16][17], enhance the potential of clinical decision support [18], and support the management of hospital workflows [19,20]. Thereby, AI offers the possibility to support physicians in delivering high-quality medicine and increasing medical care efficiency.…”
Section: Big Data and Ai In Medicine: Definition And Application Areasmentioning
confidence: 99%
“…An alternative method to reduce report turnaround times and promote early detection of critical findings includes worklist prioritization based on urgent findings detected by AI [26]. A study from a German university hospital simulated this concept on retrospective chest radiographs and found that turnaround times for reporting critical findings reduced from 80 min to 35-50 min [27]. In the United States, a commercial algorithm to prioritize intracranial hemorrhage resulted in reduced waiting time from 16 min to 12 min per positive case [28].…”
Section: Early Detectionmentioning
confidence: 99%
“…In addition to improving radiologist accuracy, machine learning models have the capacity to integrate with workflow systems to triage studies, identifying and serving high priority, time‐sensitive findings for faster reporting. Studies suggest that these systems reduce reporting time and alleviate radiologist workloads 28,34,35 . Triage functionality is likely to become more effective as machine learning solutions become more comprehensive; a model that only looks for a single finding (such as pneumothorax) can up‐triage cases where that pathology is identified, however, in doing so it will necessarily down‐triage cases with other serious or urgent problems (such as free sub‐diaphragmatic gas).…”
Section: Additional Benefits To Machine Learning In Cxrmentioning
confidence: 99%
“…Studies suggest that these systems reduce reporting time and alleviate radiologist workloads. 28 , 34 , 35 Triage functionality is likely to become more effective as machine learning solutions become more comprehensive; a model that only looks for a single finding (such as pneumothorax) can up‐triage cases where that pathology is identified, however, in doing so it will necessarily down‐triage cases with other serious or urgent problems (such as free sub‐diaphragmatic gas).…”
Section: Additional Benefits To Machine Learning In Cxrmentioning
confidence: 99%